2020
DOI: 10.1785/0120200041
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Previous Faulting along the 2019 Ridgecrest, California, Earthquake Ruptures

Abstract: The July 2019 Ridgecrest earthquakes in southeastern California were characterized as surprising by some, because only ∼35% of the rupture occurred on previously mapped faults. Employing more detailed inspection of pre-event high-resolution topography and imagery in combination with field observations, we document evidence of active faulting in the landscape along the entire fault system. Scarps, deflected drainages, and lineaments and contrasts in topography, vegetation, and ground color demonstrate previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Thompson Jobe et al. (2020) reported that 50%–70% of the fault strands that ruptured in 2019 correspond to neotectonics features that predate the 2019 event, including subtle scarps, vegetation lineaments, and deflected drainages. However, those investigators were only able to identify a handful of sites with clear markers that record dextral motion along the Paxton Ranch fault.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson Jobe et al. (2020) reported that 50%–70% of the fault strands that ruptured in 2019 correspond to neotectonics features that predate the 2019 event, including subtle scarps, vegetation lineaments, and deflected drainages. However, those investigators were only able to identify a handful of sites with clear markers that record dextral motion along the Paxton Ranch fault.…”
Section: Discussionmentioning
confidence: 99%
“…WorldView imagery accessed under the NextView license (©DigitalGlobe 2020). Displacement measurements from optical pixel correlation available in Gold et al (2020). Optical pixel correlation results available in Barnhart et al (2020a).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Subsequent studies have shown that many of the respective seismogenic faults have recurrence times on the order of ~3-15 ka, and that, if present, scarps from prior events are heavily degraded (Rubin and Sieh, 1997;Bell et al, 1999;Rockwell, 2000). Many of the faults that accommodated these ruptures are neither major through-going structures nor range-bounding faults (Bell et al, 1999;Jobe et al, 2020;Koehler et al, 2020). We suggest that future M7 strikeslip events in the Central Walker Lane may be similar to these events, and might occur across a series of previously recognized and unrecognized structures.…”
Section: How Shear Is Accommodated Without Major Strike-slip Faultsmentioning
confidence: 99%
“…The mainshock rupture terminated at its northern extent within the Coso volcanic field and at its southern extent ∼5 km from the Garlock fault, where it was found to have triggered creep at the surface along parts of the Garlock fault and a small cluster of seismicity (Barnhart et al., 2019; Ross et al., 2019). Field‐ and remote‐based mapping of geomorphic markers and vegetation lineaments indicate that both fault systems involved in the foreshock and mainshock show extensive evidence for faulting before their rupture in 2019 (Jobe et al., 2020), but their geologic fault slip rates currently remain unknown. The Ridgecrest sequence is also notable.…”
Section: Introductionmentioning
confidence: 99%